The impact of heavy metals that released from vehicles exhausts on some biochemical parameters in Eucalyptus and Ziziphus plants in street intersections of Baghdad city - Bilal ahmed Al-Arabi; Rushdy Sabah A.A; Ithar Kamil Abbas (Tikrit Journal of Pure Science, 2023)
The air pollution by vehicles exhaust is consider the most risk environmental problems, especially when precipitate on soil surface and transport  to the plants and entering the food chain. so that, the current study was carried out to determine the impacts of air pollution on the plants growth in traffic intersections, the study was carried out in Baghdad city, identified two regions for each of the both sides of the Rusafa and Karkh by two main sites for each region, as well as, the secondary stations in each site. the heavy metals and total suspended particles concentrations were determined in the filter paper that suffer the pollution air for 30 min. in specific sites using sniffer device. The concentrations decrease of some pollutants was noticed more than to the national and global permitted limits and the summer was the highest season in pollution during study period. Eucalyptus and Ziziphus spina Christi plants was chosen to evaluating the impacts of pollution on the plants because its being of the most common and the evergreen trees in the Baghdad s' streets. Primary metabolites content in plants was measured as total chlorophyll recorded a height concentration in August(98.631mg/gm) in Eucalyptus leaves ,while the total  protein content reached to maximum concentration (26.101 mg/gm) in both plants, either total carbohydrate content reached to (88ppm) in Eucalyptus leaves and (74.62ppm) in Ziziphus leaves and noticed that , the increase in concentration of pollutants affected on the protein and carbohydrate content. Seven phenolic compounds was diagnosed  being one of the main secondary compounds of metabolism , the increase in total phenolic content was recorded in the region that have a high concentration of carbon dioxide was reach to (6699.88ppm) in Al-Mansour(3) samples compared to the control samples was(2388.87ppm). the heavy metals concentrations in the leaves of eucalyptus and ziziphus  arranged from more to less as steady regime throughout the study period  in the following order: iron > zinc > copper > lead .